Human Dimensions of the Reintroduction of Brazilian Birds - Martins, Flávia de Campos; Engel, Mônica T.; Schulz, Francine; Martins, Cláudia S. G. (Frontiers in Conservation Science, 2022)
Wildlife reintroduction, which aims to reestablish viable populations in areas of original distribution through the release of individuals, is a tool of paramount importance for biodiversity conservation. Nevertheless, reintroductions are expensive, sensitive, and labor-intensive projects, depending on acceptability, engagement and involvement of local people to its effectiveness and success, especially considering the socioeconomic and institutional context in certain regions and the drivers of species extinction. Thus, human dimensions of wildlife are key to assure well-succeeded reintroduction projects. Despite efforts to include the social component in the reintroduction programs of threatened birds, little is known about the procedure adopted by these initiatives in terms of public involvement. The objective of this research was to analyze how the main programs of bird’s reintroduction in Brazil approach human dimensions in their different stages. We analyzed the National Action Plans, the Brazilian management participatory instrument for threatened species, along with further secondary data available (peer review, grey literature, technical reports) and interviews with researchers leading those projects. Fifteen participants of the Brazilian bird reintroductions projects provided data that helped us to find out that, in general, efforts have been made to integrate local people to bird reintroduction programs. However, the actions are designed isolated and fragmented, probably either because human dimensions are not considered as important as other topics of the action programs or because of the novelty and complexity of the subject for managers and researchers, much more familiarized with biology and ecology. This represents the greatest challenge to the success of reintroduction programs. Nevertheless, no formal protocol, designed, assessed and approved by experts was found for any of the stages of this project or to any of the others. The relevance of stakeholders engagement for biodiversity conservation determines the recommendation of this study, that is for a leveling of human dimensions assessments with biology and ecology research in reintroduction projects.